Contrasting housing supply in Ireland, Northern Ireland and the rest of the United Kingdom - Disch, Wendy; Egan, Paul; Kenny, Eoin; McQuinn, Kieran (ESRI, 2024)
This report examines the Irish, Northern Irish, Welsh, Scottish, and English residential markets with a particular focus on their capacity to increase housing supply over the short to medium term. Our approach compares and contrasts how differences across the housing markets, in key costs of production, the regulatory environment and economic dynamics, have impacted the supply of housing. The report suggests that across all housing markets, but particularly in the Irish case, the traditional financial sector does not appear to be able to provide the requisite amount of credit for the level of housing activity which has been deemed necessary to meet the underlying structural demand for housing. With this in mind, increased Government investment in the form of expanding the level of social and affordable stock of housing available emerges as a key finding across all markets. The report highlights labour shortage in the construction sector as a key challenge for the expansion of housing supply across all housing markets discussed, with particular concern noted for the Northern Irish and overall UK markets related to the implications of Brexit and the UK’s withdrawal from the European Union which makes it more difficult for net immigration into the UK. With regard to planning systems, the report highlights strong similarities across housing markets where Local Authorities formalise development plans based on a housing strategy that is conceived at a national level. The report therefore suggests a greater degree of aggregation may be more practical in devising and implementing such development plans. The report highlights that the role of private developers across Ireland, Northern Ireland, Wales, Scotland and England, and how they operate in the market for land, is somewhat idiosyncratic compared to other European housing models. The report suggests that greater regulation in the provision of land for housing could help to reduce the role played by speculation in land prices, and hence lower the cost of a key factor of production. While the empirical section finds differing levels of relationships between supply and demand of housing across the various markets, the results presented in this report suggest that the higher the percentage increase of people employed in the construction sector, the more responsive the level of investment to a change in house prices. This suggests that a housing market with a greater increase in construction workers is less likely to face bottlenecks in different segments of the market in response to an increase in housing demand. This has interesting implications with regard to the construction industry’s capacity to meet the observed shortfall in supply witnessed particularly in Ireland and Northern Ireland. Finally, the report highlights the adoption of modern methods of construction (MMCs) and the importance of training and educational schemes, across both the Irish and Northern Irish markets, as a means of improving productivity levels in the construction sector in meeting climate action targets and increasing housing delivery on the Island of Ireland.